KEBIJAKAN MEWUJUDKAN PERAN DAN NORMA GENDER PADA KONDISI VIRUS COVID-19 - Hasuri Waseh; Rangga Galura Gumelar (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2022)
The Covid-19 Corona virus where getting up at the moment, has changes in many aspects such as social, economic and cultural. The impact of pandemic Covid-19, we can feel indirectly the different influence between men and women. In the context of patriarchal gender norms, the existence of men is always in the position as the main breadwinner. In this situation, the government made a policy by enforcing all work to be done at home, in purpose to break the chain of virus transmission. This policy has an impact on men staying at home, so they cannot fulfill their gender norms as breadwinners and on the other hand the workload of women in the household is getting bigger. Through qualitative and quantitative approaches in the postpositivistic paradigm, this study tries to see how the policies that have been carried out by the Serang City Government in realizing gender roles so that there is no inequality and oppression for women. The results of the study show that so many cases of violence that occurred during this pandemic, then there was no direct policy taken by the Serang City Government to protect women, which was only limited to assistance and consultation for those who had violence problems. Keywords : Gender Norms and Roles, Policies, Covid-19, Serang City